Pelatihan Penerapan Model PBL dan PjBL bagi Guru Sekolah Dasar Negeri di Kota Palangka Raya - Manesa; Sion, Holten; Debora; Nyoto; Nugroho, Piter Joko; Hartani; Anggriani, Yulia; Yulianti, Indah (LPPM Universitas Palangka Raya, 2024)
This training aims to improve the ability of public elementary school (SDN) teachers serving in the suburbs of Palangka Raya City to apply Problem-Based Learning (PBL) and Project-Based Learning (PjBL) learning models. The training method used includes an interactive approach through group discussions, practical simulations, and direct guidance in designing PBL and PjBL-based teaching modules. The results of this training activity show a significant increase in teachers' conceptual understanding and practical skills related to the application of PBL and PjBL in learning in elementary schools. The trainee teachers became more skillful in designing innovative teaching modules that are in accordance with the principles of PBL and PjBL and showed increased confidence in managing classes with these approaches. In addition, the formation of a learning community among teachers shows a commitment to continue sharing knowledge and experiences, supporting the sustainability of PBL and PjBL implementation consistently in schools. It is hoped that the impact of this training can contribute to improving the quality of teaching and learning outcomes of students in peripheral elementary schools in Palangka Raya City.